Manufacturing an illusory consensus? A bibliometric analysis of the international debate on education privatisation. (January 2019) - Verger, Antoni; Fontdevila, Clara; Rogan, Ruarri; Gurney, Thomas
Highlights: Studies reporting negative effects of privatisation outweigh those finding a positive impact. International agencies reviewing evidence on privatisation exhibit contrasting citation patterns. Some agencies draw on a body of literature poorly connected to scholar research. The selectivity of references is indicative of a tactical use of evidence with legitimizing purposes. Abstract: As one of the most polarised areas in education research, the education privatisation debate generates opportunities for knowledge-brokers to promote their preferred policy alternatives. Based on bibliometric analysis techniques, this paper maps the configuration of the academic debate on privatisation, and explores how it is connected with the references mobilized by a group of international agencies located at the interstices of the research and policy fields. Our findings suggest that, when confronted with certain incentives, some international agencies use evidence in a selective and tactical way as a means to support their pre-established policy pReferences.